Primary bladder adenocarcinoma versus metastatic colorectal adenocarcinoma: a persisting diagnostic challenge - Roy Somak; Smith Matthew A; Cieply Kathy M; Acquafondata Marie B; Parwani Anil V (BMC, 2012)
Abstract Aim This study attempted to distinguish primary bladder adenocarcinoma (PBA) from metastatic colonic adenocarcinomas (MCA), which is a difficult diagnostic and clinical problem. Methods Twenty-four cases of bladder adenocarcinomas (12 primary & 12 metastatic colorectal) were included in the study with urothelial carcinoma (UC) and colonic adenocarcinoma (CA) as controls. A panel of immunohistochemical (IHC) stains along with fluorescence in-situ hybridization (FISH), using the UroVysion probe set, was performed. Results The majority of the PBAs presented with advanced disease. Enteric histologic subtype was the most common morphological variant. Strong nuclear with cytoplasmic-membranous staining of β-catenin was seen in 75% of MCA and only 16.7% PBA (<10% staining cells). Although abnormal nuclear staining with E-cadherin was seen in both PBA and MCA, it was more frequent in former. CK-7, CK-20, villin and CDX-2 stains were not helpful in distinguishing the two entities. FISH did not reveal any unique differences in chromosomal abnormality between the two groups. Conclusion Although there was a statistically significant difference in β-catenin and E-cadherin staining between two groups, we did not find any IHC or FISH marker that was specific for PBA. Distinction between PBA and MCA remains a diagnostic problem and clinical correlation is vital before rendering a diagnosis. Virtual slides The virtual slides for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1393156268152357